ANALISIS KARAKTERISTIK JARINGAN DAUN DENGAN TINGKAT SERANGAN PENYAKIT BLAS (Pyricularia oryzae Cav.) PADA BEBERAPA GENOTIPE PADI (Oryza sativa L.) - Dwi Agustina, Elsa (JURNAL AGRI-TEK, 2018)
The use of blast resistant varieties is an effective and environmentally friendly control. The planting of several resistant varieties with different sources of resistance genes can prevent the epidemic cycle of blast disease. Blas disease can reduce rice production by up to 70% and infect all plant stadia stadia such as leaves, shoots, panicles, but rarely found on leaf midrib. Based on the research, it can be concluded that (1) 21 test genotypes showed different responses to leaf blast disease, this can be seen from incubation period, attack intensity and endurance category; (2) The intensity level of genotype K-203, Mekongga, K-56, CMS B, K-76, K-32, K-157, Cibogo, Ciherang, Hipa 8, IR 64, K-162, K-137, K-67, K-132, K-79, K-160 and Inpari 13 correlated with epidermal thickness, but on IR 64 ss genotype this did not occur. Keywords: leaf tissue, leaf blast disease (pyricularia oryzae cav.),  rice genotype (oryza sativa l.)